Peningkatan Motivasi Dan Keaktifan Belajar Matematika Melalui Strategi Pembelajaran Tipe NHT (Numbered Heads Together)(PTK Pada Siswa Kelas VIII G MTsN Gondangrejo Semester GenapTahun 2015/2016) - Setiawan, Arif, Dra. Sri Sutarni, M.Pd (2016)
ABSTRACT Arif Setiawan/ A410120080. Peningkatan Motivasi dan Keaktifan Belajar Matematika melalui Strategi Pembelajaran Tipe NHT (Numbered Heads Together) (PTK Pada Siswa Kelas VIII G MTsN Gondangrejo Semester Genap Tahun 2015/2016). Skripsi. Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. 2016. The purpose of this study were 1) to increase motivation and activity of learning mathematics class VIII G MTsN Gondangrejo second semester of the 2015/2016 year), 2) to increase motivation and activity of learning mathematics through NHT learning strategy at class VIII Semester G MTsN Gondangrejo year 2015/2016. This study uses classroom action research. Source data comes from teachers and students. Implementation of class actions implemented over two cycles, each cycle consisting of two meetings. Methods of data collection is done through observation, interviews and document review. The analysis technique used to analyze the data collected by the data collection techniques, data reduction, data presentation, and conclusion. The validity of the data with source triangulation and triangulation techniques. The results of this study showed an increase students' motivation and activeness. It can be seen from the increase in the indicators: 1) students are encouraged curiosity about the sheets keja of prior actions as many as 12 students (30%) to as many as 30 students (75%), 2) students are encouraged to complete the worksheet on the prior actions as much as 12 students (30%) to a total of 32 students (80%), 3) the students are challenged to get the maximum score on the prior action as many as 11 students (27.5%) to as many as 26 students (65%), 4) students are active in asking from before the measure as many as 12 students (30%) to as many as 26 students (65%), 5) students are active in answering of prior actions as many as 10 students (25%) to as many as 28 students (70%), and 6) students actively in the work group of prior actions as many as 12 students (30%) to a total of 32 students (80%). The conclusion of this study is a learning strategy NHT (Numbered Heads Together) can increase motivation and activeness of eighth grade students learn math G MTsN Gondangrejo second semester of the year 2015/2016. Keywords: learning motivation, active learning, numbered heads together.